Analisis Yuridis Kedudukan dan Efektivitas Regulasi Badan Permusyawaratan Desa dalam Menjalankan Fungsi Pengawasan Konstitusional terhadap Akuntabilitas Kinerja Kepala Desa - Janne Alfarizi; Chandra Jaya Agung Pratama; Khikmawanto Khikmawanto (Pemuliaan Keadilan, 2026)
The Village Consultative Body (BPD) plays a strategic role in the system of checks and balances at the village government level under Law No. 6 of 2014 on Villages. However, in practice, this institutional oversight function often faces various regulatory and operational obstacles. This study aims to conduct an in-depth legal analysis of the BPD’s authority to oversee the performance of the Village Head. Through a normative legal approach supported by a literature review of various regulations, this study examines the operational limitations and the effectiveness of BPD oversight. The research findings indicate that the BPD oversight norms stipulated in Ministry of Home Affairs Regulation No. 110 of 2016 remain administrative-preventive in nature and have not yet addressed the realm of repressive sanctions. The primary obstacles to oversight stem from the low legal literacy of BPD members, the lack of transparency in village executive reporting, and the suboptimal technical guidelines for oversight at the regional level. Consequently, the oversight that takes place tends to be merely a formality and is prone to triggering horizontal conflicts with the Village Head. To optimize this control function, regulatory strengthening is required through the standardization of Village Head performance parameters and the continuous enhancement of BPD members’ legal capacity. Strong synergy between the BPD and the village community is the key to realizing accountable and transparent village governance.